Olfactory speed – Temporal odor processing of paired stimuli. (4th June 2015) - Schriever, V.A.; Frenzel, C.; Wernecke, S.; Croy, I.; Valder, C.; Hummel, T.
Highlights: Temporal processing of olfactory stimuli is fairly slow. Approximately 4 s are needed between two olfactory stimuli to be perceived separately. Olfactory event-related potentials can be obtained in response to subjectively not-perceived olfactory stimuli. Abstract: Objectives: Compared to other senses, temporal perception of odors seems fairly slow. In addition it has been shown in previous studies that even not consciously perceived odors could influence our behavior. Aim of the current study therefore was to study the interstimulus interval (ISI) length, which is necessary between two repetitive stimuli to be able to perceive them separately. The additional aim focused on observing central odor processing of not perceived odorous stimuli. Materials and methods: The study was divided into three parts. In each part healthy, normosmic volunteers were included. In part I and II stimulus pairs (CO2, H2 S, orange and phenyl ethyl alcohol (PEA)) were presented to the subjects via a computer-controlled olfactometer with short ISI of 0.6–9 s. The decision whether one or two stimuli were perceived was recorded. In addition the influence of odor valence, trigeminallity and concentrations was observed. In part III olfactory event-related potentials (OERPs) to perceived and not-perceived odors were recorded. Results: The two stimuli of a stimulus pair were perceived separately more often with increasing ISI length. This increase was significant until an ISI between the stimuli of 4 s. Odor intensity, pleasantness, trigeminallity and sex had no major influence on this. In addition we were able to observe that OERPs are less often detected in response to not perceived olfactory stimuli. However, the presence of OERP in response to not perceived stimuli in more than half of the cases indicated that even not perceived stimuli are centrally processed.